Diet Quality, Nutrient Intake, and Estimated Iron and Zinc Bioavailability in Stunted and Normal Toddlers in Bogor Regency, Indonesia: A Comparative Study - Rahmauldianti Safitri; Cesilia Meti Dwiriani; Dodik Briawan (Media Publikasi Cendekia Indonesia, 2026)
There are still limited studies assessing nutrient intake, especially micronutrients, among stunted children under five. Indonesia also does not yet have official indicators to evaluate diet quality in young children. This study aimed to analyze the differences in diet quality, macro-and micronutrient adequacy, and estimated bioavailability of zinc and iron in stunted and normal toddlers. Using a comparative cross-sectional design, the study was conducted at Purwasari and Kampung Manggis Community Health Centers from August 1 to 26, 2025, involving 60 stunted and 60 normal children. Diet quality was assessed using an Indonesian-adapted Healthy Eating Index (HEI 2–5 years). The results showed significant differences between stunted and normal toddlers in maternal education (p=0.001), paternal education (p=0.043), paternal occupation (p=0.045), parity (p=0.028), per capita income (p=0.006), birth weight (p=0.003), and history of infectious diseases (p=0.019). Diet quality components that differed significantly included vegetables and green vegetables (p=0.031), fruits and fruit juices (p=0.009), and dietary diversity (p=0.003), with normal toddlers demonstrating higher scores. Normal toddlers also had significantly higher adequacy of macronutrients and micronutrients (p<0.05). Estimated iron and zinc absorption were significantly lower among stunted toddlers (iron p=0.019; zinc p=0.010), although overall iron and zinc bioavailability categories did not differ significantly between groups. Stunting among Indonesian toddlers is associated with unfavorable socioeconomic conditions, lower birth weight, history of infectious diseases, needs improvement diet quality, and reduced estimated micronutrient absorption. Interventions should prioritize improving dietary quality, increasing vitamin C intake to enhance iron absorption, and limiting dietary inhibitors such as tea, alongside broader strategies addressing household socioeconomic factors and child health.